2020
DOI: 10.7759/cureus.11333
|View full text |Cite
|
Sign up to set email alerts
|

Kinesiophobia in a Patient With Postoperative Midshaft Fracture: A Case Report of Its Impact on Rehabilitation in a 16-Year-Old Girl

Abstract: Kinesiophobia is an irrational and debilitating fear of physical movement and activity resulting from a feeling of vulnerability to painful injury or re-injury. According to the concept of avoidance of fear, pain is interpreted as threatening, which can trigger pain-related fears and anxiety leading to avoidance behavior. Avoidance action involves a process/period characterized by a person stepping back from undertaking daily tasks like exercise, socializing, and work, which increases the intensity of the pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 9 publications
(14 reference statements)
0
15
0
Order By: Relevance
“…The results showed a 6 weeks physical therapy rehabilitation showed a good improvement in the patient's condition [10]. The planned physical therapy programme was helpful in reducing the kinesiophobia in patient [11]. Physiotherapeutic intervention used to improve the overall condition of the patient [12].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed a 6 weeks physical therapy rehabilitation showed a good improvement in the patient's condition [10]. The planned physical therapy programme was helpful in reducing the kinesiophobia in patient [11]. Physiotherapeutic intervention used to improve the overall condition of the patient [12].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic changes in the dystrophin gene make it impossible for the body to produce the protein dystrophin, which is essential for muscle contraction. Damage to muscles occurs once the muscle contracts, and is healed but proteindeficient, leading to a muscle that is still weak [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…To help restore normal muscle function, facial muscle strengthening exercises and modalities were given. In our plan, as patient impairment varies with rehabilitation, the exercise regimen transitions with time [13,14]. Few of the related studies were reported [15][16][17].…”
Section: Discussionmentioning
confidence: 99%